ANALISIS PEMBIAYAAN BERMASALAH (NON PERFORMING FINANCING) DAN KECUKUPAN MODAL (CAPITAL ADEQUACY RATIO) PADA BANK BRI SYARIAH TAHUN 2011 – 2016 - DIDIN RASYIDIN WAHYU (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2019)
In simple terms it can be said that a healthy bank is a bank that can carry out its functions properly. In other words, a healthy bank is a bank that can maintain and maintain public trust. This research was conducted to analyze financial performance using Non-Performing Financing (NPF) and Capital Adequacy Ratio (CAR) ratios. and know the NPF and CAR calculations from the data that has been presented in the BRI BRI Syariah financial statements for 2011-2016, so we can see the increase and decrease. The method used in this research is qualitative method. This research was conducted at BRI Syariah Bank using secondary data taken from the BRI Syariah Syariah annual financial statements in 2011-2016. The variables used were Non-Performing Financing (NPF) and Capital Adequacy Ratio (CAR). The results of this study note that the capital ratio or CAR during 2011 to 2016 is greater than the bank soundness assessment criteria set by Bank Indonesia of 8%, the ratio achieved by Bank BRI Syariah is categorized in the HEALTH group. While BRI Syariah NPF experienced quite noticeable fluctuations, the percentage was nearly 5% of the NPF set by Bank Indonesia. However, in its development the NPF of Bank BRI Syariah still shows a controlled figure (under 5%), which means it can be assessed HEALTHY. The conclusion of the study is based on the above explanation, then in the assessment of the level of capital adequacy (CAR) and problematic financing (NPF) in BRI Syariah Bank in 2011-2016 it can be said that the bank managed to maintain the value of the NPF and CAR ratio